Effects of Rainfall Intensity and Vegetation Cover on Erosion Characteristics of a Soil Containing Rock Fragments Slope - Bingqin Zhao; Lun Zhang; Zhenyao Xia; Wennian Xu; Lu Xia; Yongzhe Liang; Dong Xia (Advances in Civil Engineering)
Rainfall events coupled with shallow and gravelly sloping farmland have led to serious soil erosion and associated problems in the Three Gorges reservoir. Previous studies have shown that the use of vegetation is an effective way to control soil erosion. Therefore, an artificial, simulated rainfall experiment study is conducted to determine the effect of rainfall intensity and vegetation cover on runoff volume, sediment load, and runoff hydraulics characteristics. The experiment consists of seven vegetation treatments subjected to three rainfall intensities on a soil that contains rock fragments on a slope of 30°. The results indicate that the runoff volume and sediment load of the bare plot were greater than those of vegetation-covered plots under three different rainfall intensities. When Cynodon dactylon and Indigofera amblyantha were applied together, the plot displayed the best performance for soil loss control, with a reduction of 87.88%–99.11%. According to a redundancy analysis, the change in rainfall intensity had the least impact on the Reynolds number and the runoff volume of the herb-shrub mixed plot in this study. These findings suggest that the effect of combining Cynodon dactylon and Indigofera amblyantha and increasing the vegetation coverage is an effective solution for soil and water loss conservation. The application of this method can alleviate environmental stress on the Three Gorges reservoir.